A novel hydraulic excavator boom driving system with high efficiency and potential energy regeneration capability. (15th June 2018) - Ge, Lei; Quan, Long; Li, Yunwei; Zhang, Xiaogang; Yang, Jing
Highlights: A novel asymmetric pump is used to improve the efficiency of boom. The pump can realize throttle-less driving and efficient energy recovering. 82.7% of the boom potential energy could be recovered. The system can significantly improve the working performance. The energy efficiency of the boom system can be further improved. Abstract: This paper proposes a new hydraulic excavator boom driving system using novel asymmetric pump to reduce energy consumption. Due to large throttling loss and gravitational potential wasting, conventional hydraulic excavator boom driving system has very low energy efficiency. This paper aims to improve the energy efficiency of the hydraulic excavator by reducing throttling loss and regenerating potential energy directly based on a novel pump controlled system. The system under consideration utilizes a novel asymmetric pump which has three ports, of which two are connected to the hydraulic cylinder, and the other one is connected to an accumulator. Thus, this system can regenerate the potential energy directly and can basically match the unequal flow rates of the single rod cylinder. The structure and working principle of the asymmetric pump controlled single rod cylinder system are studied in depth in this paper. To better demonstrate the performance of the proposed system, the popular independent metering circuit, which has been proposed to improve the efficiency of boom system, is used as a comparison. Moreover, experimental results of the two systems have been obtained based on a real 6-ton hydraulic excavator. The boom driving system of the excavator was first modified to the independent metering circuit to conduct experiment, and afterwards was modified to the proposed system. Experimental results show that, about 82.7% of the potential energy could be regenerated and reutilized by the proposed system. Compared with the independent metering circuit, the electric power consumption of the boom system during moving-up operation can be reduced by 76.1%. Furthermore, if the energy efficiency of the power source is considered, the energy consumption during the entire boom cylinder working cycle can be reduced by 75.0%. Finally, it is worth noting that the proposed system can be applied in all kinds of heavy-duty construction machineries, though only hydraulic excavator is experimented.